Crystal polymorphism in 2, 2'-bipyrimidine-based iridium(III) complexes. Issue 17 (28th November 2022) - Sanchis-Perucho, Adrián; Orts-Arroyo, Marta; Castro, Isabel; Lloret, Francesc; Martínez-Lillo, José
Abstract: Mononuclear iridium(III) complexes, NBu4 [IrBr4 (bpym)] (1 ) and [IrBr3 (bpym)(MeCN)] (2a and 2b ) [NBu4 + = tetra( n -butyl)ammonium cation; bpym = 2, 2'-bipyrimidine], have been prepared and characterized. Their crystal structures were determined by single-crystal X-ray diffraction. 1 and 2a crystallize in the monoclinic crystal system with space groups P 21 /c and P 21 /n, respectively. The 2b phase crystallizes in the orthorhombic crystal system with space group P 21 21 21 . In these complexes, each iridium(III) is six-coordinate and bonded to two (1 ) or three (2a and 2b ) nitrogen atoms from bpym and MeCN (2a and 2b ) molecules and three (2a and 2b ) or four (1 ) bromides. In all the cases, they exhibit a distorted octahedral environment. 2a and 2b display a packing polymorphism containing π···Br, C–H···Br and Br···Br intermolecular interactions. Further analyses of their crystal structures were performed through the SHAPE and CrystalExplorer programs. The electrochemical properties of 1 and 2 were investigated through cyclic voltammetry (CV) technique, with 1 showing a reversible iridium(III)–iridium(IV) redox process. UF0001